Propósito, personalidade e emoção como vias para a construção de sentidos da marca Nubank - Araújo, Cledilson Carlos dos Santos (2021)
Nubank stands out among Brazilian start-ups – not only for the more than 23 million customers reached in less than 10 years, but also for the way it has established itself among fintechs and built an emotional relationship with its customers, which is rarely seen in companies in the financial sector. That considered, this study aimed to investigate Nubank as a phenomenon in order to identify the particularities of its communication strategy and, consequently, of its branding through a case study aiming to analyze if/how subjective factors such as emotions, personality, and higher purpose of its communicated business model can contribute for the brand to be considered a lovemark (the highest level of meaning construction between a client and a brand). Thus, we analyze the emotions, and the main purpose of the Nubank business model, highlighting in its historical trajectory and apparent personality, the values, positions, and characteristics that build meaning and differentiate it from other brands. The case study was carried out using the content available on the fintech website; posts on its official profiles on Youtube, Facebook, and Instagram during September 2019; the most relevant comments in response to each of these posts; the four most popular interviews with the company's founders, available on YouTube; and an exclusive interview with a Nubank employee, who preferred to keep his identity confidential. The content was analyzed through prototypical categories that made it possible to observe the perspective of the public and the company as expressed by the brand, as well as the identification of patterns of convergence or divergence based on the knowledge established so far by David Aaker and Kevin Roberts on the construction of meaning and brand relevance. The results clearly indicate that the brand has, in different proportions, the attributes that constitute a lovemark. It was possible to see how the convergence between the theory of emotional/social benefits and the attributes that constitute a lovemark proved to be true and efficient to build meaning and significance in the relationship between the customers and the brand. Nubank seems to prioritize feelings like belonging, pride, happiness, representativeness, and inclusion, and this resonates in a significantly positive way in its customer comments. On the other hand, it was possible to perceive how a brand experience classified as “very bad” can trigger feelings of outrage, neglect, frustration, and anger, with the potential to regress all advances in approaching the brand to its customers. The brand does not seem to use the definition of brand personality, in a planned way, as the core of its branding strategy, although its higher communicated purpose proves to be very strong and coherent. If for many of its customers Nubank is already seen as a lovemark, more attention to the points of tension and/or inconsistency presented in this research can considerably increase the share of customers who love the brand.